POSTOPERATIVE ATRIAL FIBRILLATION AFTER CORONARY BYPASS SURGERY IN PATIENTS HAVING PRE-OPERATIVE HYPOALBUMINEMIA - Shah, Asaf; Memon, Rizwan Aziz; Shirazi, Zara; Ishaq, Muhammad (Journal of Ayub Medical College Abbottabad, 2023)
Background: Hypoalbuminemia commonly occurs in cardiac patients, especially in elderly patients and those with chronic congestive heart failure, and it has been associated with adverse events such as atrial fibrillation. The study aimed to determine the incidence of postoperative atrial fibrillation (POAF) in patients undergoing coronary bypass surgery (CABG) with pre-operative hypoalbuminemia in a major cardiac surgery institute in Karachi, Pakistan. Methods: This descriptive cross-sectional study included patients of any gender, aged between 30-80 years, who underwent CABG surgery and had hypoalbuminemia at the time of pre-operative assessment. Hypoalbuminemia was defined as a serum albumin level less than 3.8 mg/dL (normal range: 3.8-4.5 mg/dL). We recorded routine daily 12-lead ECGs and monitored the occurrence of POAF within 72 hours of surgery. Results: A total of 144 patients were included in the study, of which 77.8% (112) were male, and the mean age was 58.1±8.4 years. The average serum albumin levels before surgery were 3.5±0.2 mg/dL. The majority of patients, 71.5% (103), had three-vessel disease (3VD), and 20.8% (30) had 3VD with left main (LM) disease. Hypertension was observed in 70.1% (101) of the patients, diabetes in 52.1% (75), and prolonged CBP time in 61.8% (89). The frequency of POAF was 10.4% (15), and it was significantly higher in non-hypertensive and non-diabetic patients, with a crude odds ratio of 4.19 [1.39-12.65] and 8.47 [1.84-39.09], respectively. Conclusion: The study found that approximately one in every ten patients undergoing CABG experienced POAF. Surprisingly, the rate of POAF was higher among non-hypertensive and non-diabetic patients.